Case report: Successful combination of CLL1 CAR-T therapy and hematopoietic stem cell transplantation in a 73-year-old patient diagnosed with refractory acute myeloid leukemia - Zhao, Yifan; Wang, Hao; Zhang, Yu; Zhang, Yi; Zhang, Xiaomei; Zhao, Mohan; Liu, Jile; Guo, Shujing; Zhao, Mingfeng (Frontiers in Immunology, 2024)
The incidence of Acute myeloid leukemia (AML) increases with advancing age, and the prognosis for elderly patients is significantly poorer compared to younger patients. Although the combination therapy of venetoclax and hypomethylating agents has demonstrated improved prognosis in patients unable to tolerate intensive chemotherapy, there remains a therapeutic blank for those who fail to achieve remission with current treatment regimens. Here, we report the successful clinical utilization of autogenous CLL1 CAR-T therapy combined with hematopoietic stem cell transplantation in a 73-year-old patient diagnosed with refractory AML. The patient achieved morphological complete remission (CR) with incomplete marrow recovery and a slight presence of minimal residual disease (MRD) after receiving CLL1 CAR-T therapy. To further enhance the treatment and promote the recovery of hemopoiesis, we performed bridged allogenic hematopoietic stem cell transplantation (allo-HSCT) 20 days after the infusion of CLL1 CAR-T cells. The patient achieved MRD-negative CR following HSCT treatment. His primary disease maintained a complete remission status during the 11-month follow-up period. The patient encountered grade 2 cytokine release syndrome and grade 4 granulocytopenia subsequent to the infusion of CAR-T cells, while several rounds of infection and graft-versus-host disease were observed following allo-HSCT.Nevertheless, all these concerns were successfully addressed through comprehensive provision of supportive treatments. We have successfully demonstrated a highly effective and safe combination strategy involving CLL1 CAR-T therapy and allo-HSCT, which has exhibited remarkable tolerability and holds great promise even for elderly patients with AML.